A Rare Presentation of Lipoma: Case of Preputial Lipoma - Jain, Aakansh; Khan, Manal M.; Namdev, Rohit (Journal of Society of Surgeons of Nepal, 2023)
Penile lipoma itself is a very rare finding. Over which preputial lipoma is not reported previously so this case of a 33-year-old married male is probably the first documented case of preputial lipoma where it causes sexual dysfunction.